Effect of different cultural practices on production of turmeric (Curcuma longa L.) in Punjab - B S Gill, S S Manhas, (Journal of Spices and Aromatic Crops, 2012)
Field experiments were conducted at Ludhiana (Punjab) to study the effect of different cultural practices on production of turmeric (Curcuma longa L.). Number of tillers, dry matter accumulation, number of rhizomes plant-1 and yield were significantly higher when mother rhizomes were used as planting material as compared to primary and secondary fingers. Quality parameters and nutrient uptake also increased with increase in planting material size. Number of tillers, dry matter accumulation, number of rhizomes plant-1 and yield decreased significantly with delay in planting from 25th April to 25th May. Quality parameters and nutrient uptake were also better with 25th April planting. Rhizomes plant-1, yield, quality parameters and nutrient uptake were not affected by different harvesting dates. Mother rhizomes as planting material and 25th April planting resulted in maximum net return and benefit:cost ratio.